2020
DOI: 10.1002/mpr.1828
|View full text |Cite
|
Sign up to set email alerts
|

Clinical reappraisal of the Composite International Diagnostic Interview Version 3.0 in the Saudi National Mental Health Survey

Abstract: Objectives The DSM‐IV diagnoses generated by the fully structured lay‐administered Composite International Diagnostic Interview Version 3.0 (CIDI 3.0) in the Saudi National Mental Health Survey (SNMHS) were compared to diagnoses based on blinded clinical reappraisal interviews. Methods Telephone follow‐up interviews were administered using the clinician‐administered non‐patient edition of the Structured Clinical Interview for DSM‐IV (SCID) in separate sub‐samples of SNMHS respondents who screened positive for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…The instrument used for the SNMHS was the adapted WHO Composite International Diagnostic Interview (CIDI) 3.0 58 , 59 , a fully structured interview 62 that generated diagnoses based upon the DSM-IV 63 in the SNMHS. These CIDI-related diagnoses showed good concordance with diagnoses based on blinded clinician reappraisal interviews published earlier 64 , 65 . The assessed disorders were grouped into classes such as anxiety disorders (i.e., panic disorder, agoraphobia without panic disorder, social phobia, generalized anxiety disorder, post-traumatic stress disorder, obsessive–compulsive disorder, and separation anxiety disorder), mood disorders (i.e., major depressive disorder, bipolar I and II disorder), eating disorders (i.e., anorexia nervosa, bulimia nervosa, binge-eating disorder), disruptive behavior disorders (i.e., attention deficit hyperactivity disorder (ADHD), conduct disorder, oppositional-defiant disorder, intermittent explosive disorder), and substance use disorders (i.e., alcohol and drug abuse and dependence).…”
Section: Methodssupporting
confidence: 59%
“…The instrument used for the SNMHS was the adapted WHO Composite International Diagnostic Interview (CIDI) 3.0 58 , 59 , a fully structured interview 62 that generated diagnoses based upon the DSM-IV 63 in the SNMHS. These CIDI-related diagnoses showed good concordance with diagnoses based on blinded clinician reappraisal interviews published earlier 64 , 65 . The assessed disorders were grouped into classes such as anxiety disorders (i.e., panic disorder, agoraphobia without panic disorder, social phobia, generalized anxiety disorder, post-traumatic stress disorder, obsessive–compulsive disorder, and separation anxiety disorder), mood disorders (i.e., major depressive disorder, bipolar I and II disorder), eating disorders (i.e., anorexia nervosa, bulimia nervosa, binge-eating disorder), disruptive behavior disorders (i.e., attention deficit hyperactivity disorder (ADHD), conduct disorder, oppositional-defiant disorder, intermittent explosive disorder), and substance use disorders (i.e., alcohol and drug abuse and dependence).…”
Section: Methodssupporting
confidence: 59%
“…If so, our estimates of the relative burden of mental disorders on DOR are likely conservative. Another possibility is that the diagnostic instrument used (CIDI 3.0), which is known to produce conservative estimates more generally, might have been even more conservative in KSA [ 31 ]. It is noteworthy, though, that underreporting of physical disorders might have occurred as well due to the use of self-report physical disorder checklists rather than medical examinations, but we would expect this to be less of a problem than for reports of mental disorders because of the lower stigma associated with physical than mental disorders and evidence from previous research that good correspondence exists between self-reports and clinical records of chronic physical disorders [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…We focus on 12-month prevalence of five anxiety disorders (panic disorder or agoraphobia, separation anxiety or social phobia, generalized anxiety disorder, post-traumatic stress disorder, obsessive-compulsive disorder), two mood disorders (major depressive disorder, bipolar I-II disorder), two disruptive behavior disorders (attention-deficit/hyperactivity disorder (ADHD), intermittent explosive disorder), and any eating disorder (anorexia nervosa, binge eating disorder, bulimia nervosa). A clinical reappraisal study showed that CIDI diagnoses are valid but conservative compared to diagnoses based on blinded clinical reappraisal interviews with the Structured Clinical Interview for DSM-IV [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The response rate was 61%. Further details of the survey procedures can be found elsewhere (Aradati et al, 2019; Hyder et al, 2017; Kessler et al, 2020; Shahab et al, 2017).…”
Section: Methodsmentioning
confidence: 99%